Penerapan Video Tutorial Keterampilan Pembuatan Canape pada Student Club Cooking Class SDIT At-Taqwa Surabaya - Afifah Nur’aini; Nugrahani Astuti; Lucia Tri Pangesthi; Andika Kuncoro Widagdo (BADAN PENERBIT STIEPARI PRESS, 2023)
Video tutorial learning media can facilitate the teaching and learning process and can stimulate students to be active in participating in learning. This study aims to determine teacher activities, student activities, student learning outcomes, and student responses to the application of video tutorials for canape making skills in the student club cooking class SDIT At-Taqwa Surabaya. This research was conducted in class V SDIT At-Taqwa Surabaya. This type of research is a type of pre-experiment research with a